PENERAPAN PEMBELAJARAN PROJECT BASED LEARNING (PJBL) MENGGUNAKAN DOMINO KEANEKARAGAMAN HAYATI INDONESIA (DOMINOKHAI) UNTUK MENINGKATKAN KEMAMPUAN COMPUTATIONAL THINKING PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SD N PENGKOL 01 - Yusehadi, Dahestin; Veronika Unun Pratiwi; Agus Sri Antana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low computational thinking ability of the science subject of biodiversity material in grade V students of SD N Pengkol 01. This study aims to determine the application of the Project Based Learning (PjBL) model in improving the computational thinking ability of science in grade V students of SD N Pengkol 01. This study uses a Classroom Action Research (PTK) design with the Kemmis & Taggart model consisting of 4 stages, namely: (1) Planning stage, (2) Implementation stage, (3) Observation stage, and (4) Reflection stage carried out in two cycles. The subjects used in this study were 25 grade V students of SD N Pengkol 01. The types of data used are quantitative and qualitative data. The results of the study showed an increase in computational thinking ability. The average class value in cycle I reached a percentage completion of 72% and increased in cycle II by 88%. So, it can be concluded that the application of the Project Based Learning learning model can improve the computational thinking skills of class V students of SD N Pengkol 01.